VILLAGE LEVEL ENERGY UTILIZATION OF COPRA PRODUCTION BY PRODUCTS IN EASTERN VISAYAS, PHILIPPINES - Engr. Eutiquio E. Sudaria (International Coconut Community, 1989)
Coconut is one of the important crops of the farmers in Eastern Visayas. Forty‑two percent of the agricultural land of Eastern Visayas is planted to coconut. Coconut farmers are earning money mainly from the main product of coconut which is copra. The price of copra is fluctuating. Hence, there is a need for the farmers to utilize the by‑products of copra production to augment their income. The by‑products depend on the copra making practice of the farmers. For the direct splitting method where the nut with husk is split directly with an axe, combined husk with shell locally known as